THU0259 Induction of Apoptosis and Autophagy in Circulating PBMC by Microparticles from Patients with Systemic Lupus Erytematosus. (15th July 2016) - Miranda, F.; Barbati, C.; Alessandri, C.; Spinelli, F.R.; Ceccarelli, F.; Truglia, S.; Valesini, G.; Conti, F.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a systemic autoimmune disease characterized by heterogeneous clinical manifestation and a complex pathogenesis. Lymphocytes from patients with SLE display multiple alterations, including increased cell activation, abnormal apoptosis and impairment of autophagic pathway. Recently, evidence from genetic, cell biology and animal models suggested that autophagy, a major pathway for organelle and protein turnover, may play a pivotal role in the occurrence and development of SLE. Some studies showed altered profile of circulating microparticles (MPs) in SLE patients. These MPs are released constitutively and may increase as a result of cellular activation and apoptosis. Originally considered as inert debris, MPs are now known to display diverse pro-inflammatory and pro-thrombotic activities, and they are implicated in the intercellular communications. MPs can influence the course of rheumatic and other immune-mediated diseases. Objectives: The aim of our study was to evaluate the possible role of MPs purified from SLE patients on the modulation of apoptosis and autophagy in peripheral blood mononuclear cells ( PBMCs ) isolated from healthy donors. Methods: PBMCs from healthy donors were isolated by Ficoll-Hypaque density-gradient centrifugation, cultured and treated with 0.5, 2.5, 5 *10 6 MPs purified by 10 sera of active SLE for 16 h. Apoptosis was measured using FITC-conjugated annexin V (AV) and a propidium iodide (PI) apoptosis detection kit. Acquisition was performed on a FACS Calibur. Autophagy was measured by Western blot for LC3II. Results: MPs appeared capable of inducing apoptosis. Indeed, PBMCs showed significantly higher apoptosis if treated with MPs compared with untreated cells (percentage of apoptotic cells treated with 5, 2.5 and 0.5*10 6 MPs: 15, 10, 9 vs. 7%, P =0.0001, P=ns, P=ns, with respectively). Moreover, MPs increased autophagy in a dose response manner (LC3-II/β-actin ratio: 1.2, 1, 0, 6 vs. 0.5, with 5, 2.5 and 0.5*10 6 MPs, respectively P =0.0001). Conclusions: We demonstrated that MPs from SLE patients induce apoptosis in PBMCs, thereby possibly decreasing the number of circulating leucocytes. The mechanisms underlying such phenomena are not known. Some authors suggested that MPs, through the arachidonic acid pathway, may induce apoptosis. Indeed, this pathway, together with the sphingomyelinic, increase the concentration of ceramide, thus leading into apoptosis mediated by the activation of caspase 8 and by the release of downstream pro-apoptotic factors. Moreover, available data do not exclude the possibility that components of MPs other than arachidonic acid, may also contribute to the ceramide-mediated apoptosis. Finally, this is the first study addressing the relations between MPs and autophagy, suggesting an increase of this cellular event after exposure to MPs. Since an augmented autophagy has been implicated in autoimmunity, it could be of interest to target MPs in order to re-balance the autophagic processes. Disclosure of Interest: None declared